2002
DOI: 10.1002/app.11310
|View full text |Cite
|
Sign up to set email alerts
|

Microdispersion of polyphenylene ether in polyphenylene sulfide/polyphenylene ether alloy compatibilized by styrene‐co‐glycidyl methacrylate

Abstract: ABSTRACT:The polyphenylene sulfide/polyphenylene ether (PPS/PPE) alloy is desired for use as an engineering plastic. In this case, microdispersion of PPE in the PPS matrix is preferable. We have developed a new method for the preparation of a PPS/PPE alloy that has microdispersed PPE in the PPS matrix. The reactive processing of PPS with PPE gave a PPS/PPE alloy with a microdispersed PPE in the PPS matrix, using styrene-co-glycidyl methacrylate copolymer (SG) as a compatibilizer. Although the general propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 6 publications
(9 reference statements)
0
10
0
Order By: Relevance
“…It was demonstrated that the so-compatibilized interface in PPS/LCP blends significantly contributes to the enhancement of tensile properties and impact strength. 10 The second group of PPS blends is formed with conventional engineering plastics with thermal stability between 100-140 1C for long usage such as crystalline polyamide (PA) [11][12][13] and poly(ethylene terephthalate) (PET), [14][15][16] and amorphous poly(phenylene ether) 17 and polycarbonate (PC). 18 It is reported that (20/80) PPS/PA4,6 (T m of PA4,6¼295 1C) blends have a miscible region, which appears under a high shear rate at 310-320 1C 13 although the solubility parameter of PPS is extremely high (12.5 (cal cm À3 ) 0.5 ) compared with other polymers and this makes it difficult for PPS to have miscibility with other polymers.…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that the so-compatibilized interface in PPS/LCP blends significantly contributes to the enhancement of tensile properties and impact strength. 10 The second group of PPS blends is formed with conventional engineering plastics with thermal stability between 100-140 1C for long usage such as crystalline polyamide (PA) [11][12][13] and poly(ethylene terephthalate) (PET), [14][15][16] and amorphous poly(phenylene ether) 17 and polycarbonate (PC). 18 It is reported that (20/80) PPS/PA4,6 (T m of PA4,6¼295 1C) blends have a miscible region, which appears under a high shear rate at 310-320 1C 13 although the solubility parameter of PPS is extremely high (12.5 (cal cm À3 ) 0.5 ) compared with other polymers and this makes it difficult for PPS to have miscibility with other polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the microdispersion of polyphenylene ether in PPS/PPE alloy can also affect the mechanical behaviors. [143] In this study, it showed that the weld strength of PPS/SG/ PPE was found to be significantly decreased because of the increasing particle diameter.…”
Section: Pps Blending With Other Polymersmentioning
confidence: 65%
“…Thus, many approaches have been proposed to overcome these disadvantages of PPS. To modify PPS by physical blending or alloying with other polymers or with other reinforcement materials is the most common and widespread method in industrial and academic domains currently …”
Section: Blendingmentioning
confidence: 99%
See 2 more Smart Citations